Advancements in Galianthe (Spermacoceae-Rubiaceae) knowledge: complete description of G. longifolia and new records for G. thalictroides in Mato Grosso do Sul, Brazil - Florentín, Javier E.; Nuñez-Florentin, Mariela; Salas, Roberto M. (Phytotaxa, 2024)
This study presents a complete and enriched morphological description of Galianthe longifolia, incorporating previously unreported data on the characteristics of its fruits, seeds, and pollen. These attributes are of crucial taxonomic importance. In turn, the range expansion of G. thalictroides in the state of Mato Grosso do Sul, Brazil, is documented. These new findings significantly improve our understanding of the taxonomy and preferred habitats of the species.